Feasibility Interactive PowerPoint Sub-material Biodiversity Utilization Based Inventory Traditional Ceremonial Plants - Junjung, Yosefa Gelarasia; Syamswisna, Syamswisna; Yuniarti, Anisyah (Department of Biology Education Faculty of Teacher Training and Education Sebelas Maret Un, 2022)
As a result of the development of the current modernization for the next generation, namely considering ancestral culture as a feature of backward society and abandoning traditional lifestyles. These subjects can be approached though biology learning, especially on the utilization of biodiversity sub material. The existence of information delivery through interactive PowerPoint can help students as the next generation to see ancestral culture, not as a feature of backward communities. The purpose research is to determine the feasibility interactive PowerPoint learning media the sub-material the utilization biodiversity. The research method is descriptive quantitative. The research was carried out in 2 stages, namely an inventory traditional ceremonial plants the Dayak Bidayuh Tribe, Hlibuei Village, and a feasibility test interactive PowerPoint media. Through the inventory stage, we found 20 plants used by the Dayak Bidayuh tribe as ceremonial plants. Media validation consists of 6 validators, namely 3 material experts and 3 media experts. The validation results get the 3.67 by material experts and media experts of 3.65. Based on the category of validity by looking at the value of obtained, interactive PowerPoint media is suitable for use in learning biodiversity sub-material.